PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS SUMBER DAYA AIR, CIPTA KARYA DAN TATA RUANG PROVINSI SUMATERA UTARA - Daksur Poso Alisahbana Hasibuan; Safrida .; Nusantara Tarigan Silangit; Ali Asmi Lubis; Wildan Hidayat (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
This research was conducted in Dinas Sumber Daya Air, Cipta Karya dan Tata Ruang Provinsi Sumatera Utara. The population in this study were all employees in each division numbering 187 people with the samples taken just 65 people, the determination of sample collection using random sampling. Instrument or data collection techniques in this study using a multiple choice test that has been in tingakat its validity and reliability. test the classical assumption of normality test, multikolienaritas and heterokedesitas and hypothesis test uses multiple linear regression analysis, F test and T test. Validity of test results obtained rhitung rtabel for each item reliability test questions and questionnaires obtained a Cronbach alpha of each variable is 0,822 for the variable X1, 0,864 for the variable X2 and 0.859 for the variable X3 to 0.922 for the variable Y. This value is greater than the level that is significantly r-tabel 0.361. The data analysis of each variable regression equation Y = 15,086 + 0,400X1 + 0,326X2 + 0,936X3 + e. Retrieved R2 of 0.517, which means the X1,X2 and X3 explain the effect on variable Y by 51.7% while the remaining 48.3% is explained by other variables outside the research. The resulting partial test each independent variables affect the dependent variable with research significance less than 0.05, and the results of the test-simultaneous calculation of 10.707 with a 3.150 Ftabel which means Fhitung F table with a level of significant (α) 0,000 0, 05, which means that the hypothesis is accepted that Leadership, Organizational Culture and Motivation on Employee Performance at Dinas Sumber Daya Air, Cipta Karya dan Tata Ruang Provinsi Sumatera Utara.